Real-World Single-Center Comparison of the Safety and Efficacy of Entecavir, Tenofovir Disoproxil Fumarate, and Tenofovir Alafenamide in Patients with Chronic Hepatitis B - Sara Jeong (Karger Publishers, 2021)
Introduction: Chronic hepatitis B (CHB) is a major cause of chronic liver diseases and tenofovir disoproxil fumarate (TDF), tenofovir alafenamide (TAF), and entecavir (ETV) are recommended as primary treatments. This study aimed to evaluate the efficacy and safety of ETV, TDF, and TAF in a real-world clinical setting. Methods: In this retrospective cohort study, a total of 363 CHB patients who were treated with ETV (n = 163), TDF (n = 154), or TAF (n = 46) from July 2007 to September 2019 were enrolled. Results: Median patient age was 51 years and 66.4% of patients were male. Median duration of treatment with ETV, TDF, or TAF was 49.0 months (interquartile range, 27.0–74.0 months). In terms of safety, cholesterol was mildly increased in the ETV and TAF groups and significantly lowered in the TDF group than baseline (p < 0.001). There was no significant difference in liver cirrhosis-related complications among the 3 groups at 48 weeks (p = 0.235). Hepatitis B e antigen seroconversion, complete virological response, and alanine aminotransferase normalization at 48 weeks as measures of treatment efficacy were not significantly different among the 3 groups (p = 0.142, 0.538, and 0.520, respectively). There was also no significant difference in cumulative incidence rate of hepatocellular carcinoma (HCC) between the ETV and TDF groups (p = 0.894). Conclusions: ETV, TDF, and TAF were safe antiviral agents and showed similar antiviral effect for CHB at 48 weeks. Cirrhosis-related complications and annual HCC incidence rates did not differ significantly between the ETV and TDF groups over the 48 week follow-up period.